Tecnologias digitais como meios de ressignificação da prática de professores de língua portuguesa, em tempos de covid-19, em escolas municipais de Manaus (AM) - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
This research aims to understand the perception of Portuguese language teachers working in elementary schools at Semed-Manaus about the use of digital technologies in their pedagogical practice, based on the context of the covid-19 pandemic. Every day, technologies become indispensable for social practices, as well as their use in the classroom context, which includes new literacies. However, it was the pandemic scenario that led to this more effective use by teachers during remote classes, avoiding complete social isolation and allowing interaction, work, and study. The theoretical basis of this research deals with the history of the Portuguese language subject and its presence in current educational documents, directing it towards the use of technologies (Bagno, 2012; Brasil, 2018; Bunzen, 2011; Shigunov Neto; Maciel, 2008; Pietri, 2012; Soares, 2012; among others); digital contemporaneity (Castells, 2022; Lévy, 1999; Xavier, 2013; among others); the phenomenon of literacy (Kleiman, 1995; Soares, 2012; Rojo, 2020; Street, 2014; Xavier, 2013); digital literacy and its conceptions (Coscarelli; Ribeiro, 2014; Dudeney; Hockly; Pegrum, 2016; Soares, 2002; Zacharias, 2020; among others); and teacher training for digital literacy (Buzato, 2006; Xavier, 2007). This research work is part of Applied Linguistics (Kleiman, 2007; Moita Lopes, 2006; Oliveira, 2019), has a qualitative approach (Bogdan; Biklen, 1994), and is characterized as a comparative study (Cervo; Bervian; Silva, 2007). Data analysis (Bardin, 2016) revealed a teacher perception of the importance of using digital technologies in Portuguese classes. On the other hand, technologies are still used as tools to transpose activities from print to the virtual environment, prioritizing school literacy, without considering the varied reading and writing practices that emerge from digital environments. As for initiatives for digital literacy, they mainly come from the teachers themselves in the exchange of information and knowledge with other colleagues and in their skills as users. Regarding the training courses, it was observed that they were more focused on clearing up doubts and suggesting lessons using the tools than on contributing to the teachers' digital literacy.
Keywords: .; LINGUISTICA, LETRAS E ARTES: LINGUISTICA; Tecnologias digitais; Perspectivas docentes; Ensino em contexto de pandemia